Предмет: Алгебра,
автор: Niknneim113
(x+4) -(x-3)(x-5) при x= одной шестой (1/6)
Решите пожалуйста, срочно
Ответы
Автор ответа:
0
( Х + 4 ) - ( Х - 3 )( Х - 5 ) = Х + 4 - ( х^2 - 5х - 3х + 15 ) = Х + 4 - х^2 + 8х - 15 = - х^2 + 9х - 11
Х = 1/6
- ( 1/36 ) + ( 9/6 ) - 11 = - ( 1/36 ) + 1 1/2 - 11 = - 11 1/36 + 1 18/36 = - 10 37/36 + 1 18/36 = - 9 19/36
Х = 1/6
- ( 1/36 ) + ( 9/6 ) - 11 = - ( 1/36 ) + 1 1/2 - 11 = - 11 1/36 + 1 18/36 = - 10 37/36 + 1 18/36 = - 9 19/36
Похожие вопросы
Предмет: Українська мова,
автор: varvarukandrij0
Предмет: Математика,
автор: aassllaann1993737379
Предмет: Українська література,
автор: ppaura
Предмет: Литература,
автор: curilenkolena0